Development and Validation of a Brief Measure of Eating Compulsivity (MEC). (6th December 2017) - Schroder, Ria; Sellman, John Douglas; Adamson, Simon
ABSTRACT: Food addiction is increasingly being recognised as a contributory factor in overweight and obesity. Management of eating compulsivity, a key component of food addiction, may assist greatly in the successful treatment of obesity. Measurement of food addiction and its core characteristic of eating compulsivity is fundamental to increasing understandings of the concept of food addiction, its prevalence among people with and without obesity and its utility within a treatment context. The current study describes the development and initial validation of a brief measure of eating compulsivity that can be used within clinical and research settings to establish a person's level of eating compulsivity. Sixty five participants with a BMI ≥30 (mean BMI 38.1) were recruited from a general population sample within Christchurch, New Zealand. Participants completed the test version of the Measure of Eating Compulsivity (MEC) and the Yale Food Addiction Scale (YFAS) as well as providing self-reported measures of height and weight. The 10-item MEC was developed. This measure was shown to have excellent internal consistency (Cronbach's alpha =.946), based on a single factor accounting for 67.4% of the variance and excellent test-retest reliability (r =.923). MEC10 score was strongly predictive of being categorised as having food addiction based on the YFAS, although not associated with BMI. This brief tool is likely to have high utility in clinical and research settings and requires further validation with a range of populations including those with and without obesity, binge eating disorder and other eating disorders.